Assessing the Psychometric Properties of the Differentiation of Self Inventory-Revised for Asian-American Bicultural Adults. Issue 1 (1st January 2017) - Lee, Hsin-Hua; Johnson, Rachel W.
ABSTRACT: Differentiation of self is the cornerstone of Bowen's (1978) theory, and is commonly assessed by the Differentiation of Self Inventory-Revised (DSI-R; Skowron & Schmitt, 2003 ). To establish the cross-cultural validity of the theory and the DSI-R, the authors sampled 315 Asian-American bicultural adults. A confirmatory factor analysis showed that the original four-factor solution did not provide an adequate fit to the current data. Subsequently, an exploratory factor analysis suggested a 34- item, three-factor model, and the new factor structure yielded strong reliability coefficients. Moreover, regression analyses demonstrated that increased levels of differentiation significantly correlated with fewer symptoms of generalized anxiety.